Pannexin 1, an ATP Release Channel, Is Activated by Caspase Cleavage of Its Pore-associated C-terminal Autoinhibitory Region - Sandilos, Joanna K. (American Society for Biochemistry and Molecular Biology, 2012)
Pannexin 1 (PANX1) channels mediate release of ATP, a “find-me” signal that recruits macrophages to apoptotic cells; PANX1 activation during apoptosis requires caspase-mediated cleavage of PANX1 at its C terminus, but how the C terminus inhibits basal channel activity is not understood. Here, we provide evidence suggesting that the C terminus interacts with the human PANX1 (hPANX1) pore and that cleavage-mediated channel activation requires disruption of this inhibitory interaction. Basally silent hPANX1 channels localized on the cell membrane could be activated directly by protease-mediated C-terminal cleavage, without additional apoptotic effectors. By serial deletion, we identified a C-terminal region just distal to the caspase cleavage site that is required for inhibition of hPANX1; point mutations within this small region resulted in partial activation of full-length hPANX1. Consistent with the C-terminal tail functioning as a pore blocker, we found that truncated and constitutively active hPANX1 channels could be inhibited, in trans, by the isolated hPANX1 C terminus either in cells or when applied directly as a purified peptide in inside-out patch recordings. Furthermore, using a cysteine cross-linking approach, we showed that relief of inhibition following cleavage requires dissociation of the C terminus from the channel pore. Collectively, these data suggest a mechanism of hPANX1 channel regulation whereby the intact, pore-associated C terminus inhibits the full-length hPANX1 channel and a remarkably well placed caspase cleavage site allows effective removal of key inhibitory C-terminal determinants to activate hPANX1.